Integrative Thematic Learning Praxis of PPKn at MI Miftahul Huda Jepara - In’ami, Moh; Syarifah; Abdillah, Syaik; Bambang; Ericawati, Rosita Oktafiana (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2022)
This research aims to find out the implementation of integrative thematic learning of PPKn subject at MI Miftahul Huda, find out the obstacles that arise in carrying out integrative thematic learning of PPKn subject at MI Miftahul Huda, and knowing solutions in dealing with integrative thematic learning problems of this subject. In order to achieve the above goals, researchers use field research with a qualitative approach. Data sources in the study used primary and secondary data sources. The subject of the study was a grade 1 teacher of MI Miftahul Huda. Data collection techniques are in the form of observation, interviews, and documentation. Test the validity of the data through readability and triangulation tests. Data analysis techniques in the form of data collection, data reduction, data presentation, and drawing conclusions. The results showed that classroom management was not optimal, low reading and writing skills, inactivity of students in learning, less interesting learning methods, and insufficient time allocation. The solution taken by the school in dealing with this problem is to hold training for teachers, warn various methods, media, and varied learning strategies, and provide additional hours to students who are slow to read and do not understand the learning material.